Pengaruh Kontrol Diri dan Academic Self-Efficacy Terhadap Academic Burnout Pada Mahasiswa - Akmal Maulana; M Jihad Intifada; Rindi Agusti Candra; Lucky Purwantini (STIKes Ibnu Sina Ajibarang, 2025)
Students who have difficulty handling lecture problems efficiently are at risk of experiencing mental fatigue. Academic burnout can refer to stress, feelings of burden, and other psychological feelings that arise when students go through the lecture process. This research aims to analyze the influence of self-control and academic self-efficacy on academic burnout in students at Universitas Islam 45 Bekasi. A total of 134 students at the Universitas Islam 45 Bekasi from various study programs were used as research subjects. The sampling technique used is probability sampling with a sampling method using simple random sampling, the data collection technique in this research uses a psychological scale, the type of scale the researcher uses is the Likert scale. The data analysis techniques used are statistical tests such as descriptive tests, normality tests, hypothesis tests, and multiple linear regression tests. The results of this research show that there is an influence of self-control and academic self-efficacy on academic burnout in students at Universitas Islam 45 Bekasi.